Belowground systems in tropical savanna: Fabaceae morphoanatomical traits and their relation to fire - Leal, A. S. [UNESP] (2024)
Post-fire regeneration characterizes woody vegetation of the Cerrado. Several species (e.g., from the Fabaceae) can resprout after fire due to the presence of storage bud-bearing belowground structures, such as xylopodia, having the capacity to rapidly allocate resources for the formation of new aboveground shoots, an advantage in fire-prone ecosystems. Therefore, we evaluated the morphoanatomical structure of the belowground organs, buds and their storage to elucidate fire-related functional traits in relation to regeneration. Besides the strong capacity of plants with xylopodia to resprout and/or their associated root suckers to propagate laterally, they also provide protection against pathogens, through the presence of defence compounds. We evaluated the morphoanatomy and performed histochemical tests with the belowground organs of eight legume species collected in open savannas in Central Brazil. Two species presented a taproot tuber and the six remaining species had a xylopodium as belowground organ. All xylopodia had buds on their upper portion. These organs were basically composed of lignified tissue, containing defence (phenolic compounds and lipidic substances), and storage (starch) substances. All xylopodia were associated to tuberous roots, and in two species these roots were also root suckers. Thus, the presence of belowground storage organs, in combination with stored defence compounds, likely facilitates the persistence of the investigated legumes in fire-prone ecosystems.